50 Incremental diagnostic value of cardiovascular magnetic resonance in young adult survivors of sudden cardiac arrest. (5th June 2017) - Tsao, Adam; Lota, Amrit; Wassall, Rebecca; Baksi, John; Alpendurada, Francisco; Nyktari, Eva; Gatehouse, Peter; Firmin, David; Cook, Stuart; Ware, James; Cleland, John; Pennell, Dudley; et al.
Abstract : Background: The prevalence of underlying cardiovascular disease in those who die suddenly varies with age (Finocchiaro et al 2016). Cardiovascular magnetic resonance (CMR) imaging can provide incremental in-vivo diagnostic value in those resuscitated from sudden cardiac arrest (SCA) but this practice is not yet supported by guideline recommendations. Method: CMR data from consecutive patients (2002–2016) referred within 6 months of resuscitated SCA were retrospectively reviewed. Patients aged >40 years of age were excluded because, for them, coronary artery disease is known to be the leading cause of SCA. Results: In total, 89 SCA survivors (mean age 28±8 years, 54% male) underwent contrast-enhanced CMR. Of these, rhythm disturbances during resuscitation were ventricular fibrillation (90%), ventricular tachycardia (7%), and a non-defined shockable rhythm (3%). The CMR study was reported as normal in 47%. The most commonly reported diagnoses (see figure A) were; dilated cardiomyopathy (18%), acute myocarditis (8%), myocardial infarction (7%), and hypertrophic cardiomyopathy (4%). Late gadolinium enhancement was present in 31%, including 5% of patients with an otherwise normal study. Eight patients (9%) were known to have a cardiovascular problem prior to SCA and 18% (n=16) had new disease identified by other investigations, such as echocardiography (see figure B). For the remainder of patients, CMR identified a new diagnosis in 26% (n=23) and excluded important structural abnormalities in 47% (n=42). The new diagnoses by CMR were early dilated cardiomyopathy (39%), acute myocarditis (30%), ARVC (13%), myocardial infarction (4%), and hypertrophic cardiomyopathy (4%). Conclusion: Contrast-enhanced in-vivo CMR findings in young adult survivors of SCA excluded important structural cardiac disease in 47%, which is similar to the rate in post-mortem studies. CMR provided incremental diagnostic value in the identification of potentially arrhythmogenic substrates due to acute myocarditis, ARVC, and dilated cardiomyopathy that may not be diagnosed by other standard investigations. These results therefore support a role for CMR in the assessment of SCA survivors.